Grolier Children's Encyclopedia 9 SOV-UNI - John Paton; Kingfisher Publications
Presents over 750 alphabetically arranged entries discussing a wide range of topics, such as stars and planets, geography, historical events, sports, presidents and kings, and the human body. Includes illustrations, photographs, and maps.